PARTICIPATING IN TEAM-BASED LEARNING - Djuraeva, Madina (Журнал иностранных языков и лингвистики, 2023)
The phrase team-based learning (TBL), which offers an engaging, structured method of small group learning that can be used in large classes, is discussed in the article. Through the unique TBL procedures, such as pre-class preparation, readiness assurance testing, problem-solving exercises, and timely feedback, student accountability is attained. TBL has been embraced by an increasing number of healthcare faculties worldwide in a variety of configurations, across various contexts and subject areas. This document offers a brief explanation of TBL as well as suggestions for teachers on how to successfully plan and implement TBL in health professional education. Additionally, it provides advice for students taking part in TBL.